On Projections in the Noncommutative 2-Torus Algebra - Eckstein, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We investigate a set of functional equations defining a projection in the noncommutative 2-torus algebra Aθ. The exact solutions of these provide various generalisations of the Powers-Rieffel projection. By identifying the corresponding K₀(Aθ) classes we get an insight into the structure of projections in Aθ.